Influence of prior cold work on age hardening of Cu-Ti-Zr alloys - Markandeya R.; Nagarjuna S.; Sarma D.S. (My University, 2025)
The influence of prior cold work on age hardening behaviour of solution treated (ST) Cu-3Ti-0·1Zr and Cu-4Ti-0·1Zr alloys subjected to cold deformations of 50, 75 and 90% has been investigated by hardness and tensile tests and optical as well as transmission electron microscopy. Hardness of Cu-3Ti-0·1Zr and Cu-4Ti-0·1Zr alloys increased from 120 and 217 HV respectively in the ST condition to 365 and 433 HV respectively on 90% cold work and peak aging. Prior cold work reduced the peak aging time of the alloys while maintaining the same temperature, i.e. 450°C. Yield strength and tensile strength of Cu-3Ti-0·1Zr alloy reached maximum values of 940 and 1029 MPa respectively on 90% deformation and peak aging, while those of Cu-4Ti-0·1Zr alloy were 1258 and 1335 MPa respectively. The microstructure of the ST and deformed alloy exhibited elongated grains and deformation bands. The maximum strength on peak aging was obtained as a result of precipitation of ordered, metastable and coherent β′, Cu 4Ti phase in addition to high dislocation density and deformation twins. These alloys were overaged as a result of the formation of incoherent and equilibrium β, Cu3Ti phase in the form of cellular structure. However, the morphology of the equilibrium β precipitate changed to globular form on high deformations. © 2005 Institute of Materials, Minerals and Mining.